Long-term survivors after failure of chimeric antigen receptor T cell therapy for large B cell lymphoma: a role for allogeneic hematopoietic cell transplantation? A German Lymphoma Alliance and German Registry for Stem Cell Transplantation analysis - Derigs, Patrick; Bethge, Wolfgang Andreas; Krämer, Isabelle; Holtick, Udo; von Tresckow, Bastian; Ayuk, Francis; Penack, Olaf; Vucinic, Vladan; von Bonin, Malte; Baldus, Claudia; Mougiakakos, Dimitrios; Wulf, Gerald; et al. (Transplantation and cellular therapy, 2023)
The outcome of patients with large B cell lymphoma (LBCL) who relapse or progress after CD19-directed chimeric antigen receptor T cell therapy (CAR-T) administered as salvage therapy beyond the second treatment line is poor. However, a minority of patients become long-term survivors despite CAR-T failure. The German Lymphoma Alliance (GLA) has proposed a hierarchical management algorithm for CAR-T failure in LBCL, aimed at allogeneic hematopoietic cell transplantation (alloHCT) as definite therapy in eligible patients. The purpose of this study was to investigate characteristics, relapse patterns, and management strategies in long-term survivors after CAR-T failure, with a particular focus on the feasibility and outcome of alloHCT. This was a retrospective analysis of all evaluable patients with a relapse/progression event (REL) observed in a previously reported GLA sample between November 2018 and May 2021. REL occurred in 214 of 356 patients (60%) who underwent CAR-T for LBCL in the previous GLA study. An evaluable dataset was available for 143 of these 214 patients (67%). Twenty-six of 143 patients (18%) survived 12 months or longer from REL, 109 (76%) died within the first year after REL, and 8 (6%) were alive but had not reached the 12-month landmark. Long-term survivors had more favorable pre-CAR-T features, had a longer interval between CAR-T and REL, and had more often received a tumor biopsy after CAR-T failure, whereas the choice of the first salvage regimen had no impact. AlloHCT was feasible in 40 of 53 patients (75%) intended and resulted in a 12 month post-transplantation overall survival of 36% in those patients who underwent transplantation with sensitive or untreated REL. AlloHCT after CAR-T failure in LBCL is feasible and may be an important contributor to long-term survival, although selection bias must be taken into account. Thus, alloHCT should be considered as a reasonable treatment option for eligible patients in this setting. However, because the overall outlook after CAR-T failure remains poor, novel effective therapeutic approaches are needed, either to allow long-term disease control per se or to improve the preconditions for successful alloHCT.(c) 2023 The American Society for Transplantation and Cellular Therapy. Published by Elsevier Inc. All rights reserved.